2010
DOI: 10.1111/j.1468-232x.2010.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Work Practices and Employee Voice: A Comparison of Japanese and Korean Workers

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
(65 reference statements)
2
32
0
Order By: Relevance
“…In support of this theoretical approach, in their literature review Cerasoli et al () found that intrinsic motivation is less important to performance when incentives are directly tied to performance (like in piece‐rate plans and commissions), and more important when incentives are indirectly tied to performance (like in profit‐sharing plans). Similarly, Bae, Chuma, Kato, Kim, and Ohashi () found that workers with group incentives created by profit‐sharing plans and grassroots innovation opportunities that originated through voice channels made productivity‐enhancing and quality‐improving suggestions more frequently than other workers.…”
Section: The Link Between Performance Pay Ev and Organizational Innmentioning
confidence: 99%
“…In support of this theoretical approach, in their literature review Cerasoli et al () found that intrinsic motivation is less important to performance when incentives are directly tied to performance (like in piece‐rate plans and commissions), and more important when incentives are indirectly tied to performance (like in profit‐sharing plans). Similarly, Bae, Chuma, Kato, Kim, and Ohashi () found that workers with group incentives created by profit‐sharing plans and grassroots innovation opportunities that originated through voice channels made productivity‐enhancing and quality‐improving suggestions more frequently than other workers.…”
Section: The Link Between Performance Pay Ev and Organizational Innmentioning
confidence: 99%
“…Informal management practices are often utilized by SMEs in order to control their employees because formal communication and control structures do not exist (Wilkinson, 1999) or are seen as bureaucratic processes (Katz, Aldrich, Welbourne & Williams, 2000). Furthermore, small firms are mostly non-unionized as a result of the paternalistic nature of their employment relationship (Bae, Chuma, Kato, Kim & Ohashi, 2011) but may incorporate more direct and informal voice channels between employer and employees (Marlow & Gray, 2005), with the level of formalization depending on a variety of internal and external factors (Hay, Beattie, Livingstone & Munro, 2001;Kotey & Slade, 2005;Sameer & Ozbilgin, 2014). Beyond the studies above, there is less understanding of how employee voice is formulated in SMEs while any reference to smaller enterprises operating in the periphery is limited.…”
Section: Employee Voice and Silence In Small And Medium-sized Enterprmentioning
confidence: 99%
“…For example, certain articles examined HPWS and its performance implications (Bae et al . ; Takeuchi and Takeuchi ), while others concentrated on the changing features of HRM practices (Hassard et al . ; Keizer ; Lee et al .…”
Section: Findings By Categorymentioning
confidence: 99%
“…Bae et al . () built on existing knowledge by comparing the data from Japanese and Korean electric appliance makers. Their notion of HPWS emphasized the factors that could enhance employee commitment.…”
Section: Findings By Categorymentioning
confidence: 99%
See 1 more Smart Citation